'Peripateticating among the mountains': Robert Southey and the Aesthetics of Pedestrian Motion. Issue 1 (April 2021) - Gonzalez, Jonathan
Abstract : Robert Southey's first published text about the Lake District, the faux travel narrative Letters from England (1807), inaugurated what became a lifelong concern with this landscape, one with pedestrianism at its very core. Ostensibly the work of the Spanish tourist Don Manuel Alvarez Espriella, Southey's Lakeland tour narrative depended on his own Letters Written During a Short Residence in Spain and Portugal (1797) – his Iberian countryside ramblings serving as a blueprint to frame his alter ego's engagement with the Lakes on foot. The motif of the outlandish Spaniard in the English fells as a turnaround of the foreign Englishman walking in Iberia, I argue, was exploited by Southey to outgrow the limitations of the picturesque as a mode of understanding and appreciating landscape. These two texts offer an insight into the direction of thought at work in peripatetic practice, evincing a markedly pedestrian Southeyan gaze that highlights each place's potential to hold multiple meanings.